PENERAPAN POLA DASAR PRAKTIS DALAM PEMBUATAN POLA BUSANA WANITA DI TEMPAT KURSUS GRIYA BUSANA MAGELANG - Ms Jumariah (Jurnal Socia Akademika, 2022)
The basic needs of clothing develop every year, especially women's clothing; this is an opportunity for fashion designers. However, making the basic clothing pattern is sometimes challenging to make it so complicated. The author tries to provide a practical and easy way of making basic patterns used as basic guidelines in making fashion patterns. This study aims to (1) determine the application of basic practical patterns in making women's clothing patterns at the Griya Clothing Magelang course, (2) determine the effect of applying basic practical patterns in making women's clothing patterns at the Griya Clothing Magelang course. The research design that the authors use is a class action research design (Classroom Action Research). In this study, 10 participants of the Griya Clothing Magelang course were the respondents. Data analysis techniques used descriptive statistical techniques, and data collection techniques used field notes and performance assessment sheets. Based on the results of the research, the authors found positive results in the application of basic practical patterns in making women's clothing patterns at the Griya Clothing Magelang course